Evaluation Program of Visit Central Java in 2013 - Dipta Rosmeykha Irianto; Susilo Utomo; Nunik Retno Herawati (Journal of Politic and Government Studies, 2015)
Central Java Provincial Government launched the Policy Visit Central Java (VJT) 2013. This is done to increase the number of tourist visits, length of stay, and tourist shopping. This policy is also expected to increase revenues. The limited support facilities and infrastructure to support tourism activities in Central Java has resulted in a decreased tourist attraction. Tourism area management pattern which does not have overall negative impact resulting decline in tourist attraction.               This study is a qualitative study with the primary objective to describe in depth the Policy Evaluation Visit Central Java 2013. Data collection techniques in this study using in-depth interviews and documentation and document analysis. Analysis of the data in this study include stage data reduction, data presentation, and data verification or conclusion.            Results of this research is the implementation of policies Visit Central Java in 2013 can be assessed to walk less than the maximum. Less the maximum policy could be assessed from the aspect of the effectiveness, adequacy, equity, responsiveness, permanence. This is because the lack of achievement of the expected target, is still a lack of promotion and information about this policy, poor infrastructure still supporting existing tourism. On the other hand this policy is able to increase revenues from tourism sector of the district / city.